Metabolomics and systems biology approaches for the investigation of endophytes – plant- interaction – a vision for their importance in biotechnology and natural product research - Weckwerth, W (Planta medica, 2011)
Plants have shaped human life forms since their rising. Plants have ever served as food and feed and have a role as one of the richest resources for natural products and lead structures in drug research. Nowadays personalized medicinal and health approaches try to adapt diets to life style. Thus, intimate knowledge of the composition of our plant-derived food is one of the next cornerstones in nutritional physiology. Together with emerging themes, such a renewable energy resources to cope with global climate changes and limited energy resources the relevance of plant biology and biotechnology becomes dramatically important in the next decades. Consequently, it can be anticipated that plant biology and applications will have even more indispensable future roles in all socio-economic aspects of our life [1]. In parallel the last 10 years have recognized a revolution in biology basically as a result of three main developments: (i) shotgun and next-generation genome sequencing, gene reconstruction and annotation, (ii) genome-scale molecular analysis using omics-technologies and (iii) computer-assisted analysis, modelling and interpretation of biological data [1, 2]. Metabolomics – the measurement of the complete small molecule fraction in a biological system – is a relatively young technology, however, has already reached an importance comparable with proteomics and transcriptomics platforms [3]. Metabolomics and proteomics emerged in parallel with the development of novel mass spectrometric techniques. Natural product research is intimately bound to these analytical procedures. Accordingly, metabolomic technology is especially suited for the analysis of a wide range of chemical diversity in biological systems. Many of these biological systems providing the widest range of chemical diversity of natural products comprise symbiotic life forms between plants, fungi and bacteria. Although known and investigated for hundreds of years, this interaction undergoes a revival of deep interest because novel tools as described above are available, especially whole-genome sequencing and genome-scale molecular profiling. Whole plant-endophyte-ecosystems can be observed in nature giving ample opportunities for the search of new natural compounds. Examples for the investigation of plant-endophyte-interactions are given and a vision is presented how the combination with novel technologies such as genome sequencing, metabolomics, proteomics and transcriptomics will increase our understanding of the mechanism of plant-endophyte-interaction and at the same time will amplify our existing portfolio of chemical diversity of natural products. References: [1] Weckwerth W (2011) Green Systems Biology – from single genomes, proteomes and metabolomes to ecosystems research and biotechnology. Journal of Proteomics in press. [2] Weckwerth W (2011) Anal Bioanal Chem 400: 1967–1978. [3] Weckwerth W (2003) Annu Rev Plant Biol 54: 669–689